Thyroid Hormone Actions and Bone Remodeling – The Role of the Wnt Signaling Pathway - Lademann, Franziska; Tsourdi, Elena; Hofbauer, Lorenz C.; Rauner, Martina (Experimental and Clinical Endocrinology & Diabetes, 2020)
Thyroid hormones are indispensable for bone development and growth. Also in adults, bone mass maintenance is under the control of thyroid hormones. Preclinical and clinical studies established untreated hyperthyroidism as a cause for secondary osteoporosis with increased fracture risk. Thus, normal thyroid function is essential for bone health. Mechanistically, thyroid hormone excess accelerates bone turnover with predominant bone resorption. How thyroid hormones affect osteoblast and osteoclast functions, however, still remains ill-defined. The Wnt signaling pathway is a major determinant of bone mass and strength as it promotes osteoblastogenesis and bone formation, while inhibiting bone resorption. So far, only few studies investigated a possible link between thyroid hormones, bone metabolism and the Wnt pathway. In this review, we summarize the literature linking thyroid hormones to bone homeostasis through Wnt signaling and discuss its potential as a therapeutic approach to treat hyperthyroidism-induced bone loss.
Keywords: thyroid hormones; thyroid disease; bone; bone turnover; Wnt signaling; sclerostin; dickkopf-1